Pengembangan Model Pembelajaran Virtual Berbasis Virtual Reality pada Kompetensi Otomotif - Ariwibowo, Bayu; Bahtiar, Fahmy Zuhda; Atika, Atika; Consuelo, Joe-Bren L (Jurnal Taman Vokasi, 2024)
This study aims to develop a virtual reality-based learning model for automotive competence. The study was conducted using research and development method with the following steps: (1) analyzing the factual model; (2) constructing a conceptual model; (3) conducting model validation; (4) revising the model and determining the hypothetical model. The results indicated that: (1) factually virtual reality was still implemented in classical manner without using the right learning model; (2) the conceptual model was organized by incorporating elements of problem solving, flipped classroom, focusing on automotive competence, providing syntax for model implementation; (3) with a score of 85.7%, validators strongly agreed to implement this model, but with some improvements; (4) the concept was improved by providing information about competencies, reinforcing the steps of flipped classroom, focusing on automotive competencies, and clarifying the model steps. In conclusion, a hypothetical model was obtained through the following steps: (1) Preparation; (2) Simulation and Confirmation; (3) Exploration or Virtual Action; (4) Review of Material Exploration; and (5) Evaluation. Steps 1 to 3 were conducted out of class while steps 4 and 5 were conducted in class. This hypothetical model is ready to be applied in further study, specifically in limited trials.